Numerical Investigation of a Steam Nozzle with Focus on Non-Equilibrium Condensation and Unsteady Flow Behavior - Dura, Hari Bahadur (Journal of the Institute of Engineering, 2019)
Present work analyses the condensation of superheated water vapor in supersonic Barschdorff nozzle. The influence of pneumatic mounts in 3D laval nozzle is analyzed using steady and unsteady two phase non-equilibrium condensation steam flow model in Ansys CFX16. Mesh independency studies in 2D model showed that at a lower inlet total temperature and very fine mesh (e.g. 100.2°C and 77k mesh elements) there is problem with the convergence using steady simulation. This is possibly due to the ability of very fine mesh to capture the small flow unsteadiness. The variation in location of Wilson’s point, Wilson’s pressure and maximum sub-cooling rate at the centerline of the nozzle is below 1.5%. The 2D CFD nucleation rate is 50% stronger and droplet diameter is 18% higher compared to the 3D CFD results. The deviation in nucleation rate and droplet diameter at nozzle outlet is the result of dissipation due to wing structure in the 3D model. Nucleation zone predicted by Ansys CFX16 is far upstream the experimental one. Different correction factors in modified nucleation model were used to fit the computed pressure distribution with the experimental one. The correction factor is dependent on boundary conditions and nozzle profile. It is thus concluded that the significance of such correction factor is not unique.